Some Notes on Monotone TSK Fuzzy Inference Systems - Kerk, Yi Wen; Tay, Kai Meng; Lim, Chee Peng (NA, 2023)
This article presents our recent research on monotone Takagi-Sugeno-Kang (TSK) Fuzzy inference systems (FISs). We outline a few remarks on the necessary and sufficient conditions for TSK-FIS to be monotone, building upon the Ordered Weighted Averaging (OWA) principle and the orness concept. Some remarks for constructing monotone TSK-FIS from monotone data, extended from our previous findings, are further elucidated.